(untitled) (Contemporary Education and Teaching Research, 2025)
This study aimed to construct a comprehensive competency evaluation index system for Master of Nursing Specialists (MNS) postgraduates to support standardized assessment of training outcomes. A preliminary set of indicators was developed through literature analysis, semi-structured interviews, and group discussions, followed by a two-round Delphi survey to refine the indicators. The analytic hierarchy process was then applied to determine the weight of each indicator. Expert response rates reached 96% and 100% in the two rounds, with authority coefficients of 0.919 and 0.927, respectively. Kendall’s W values were 0.171 and 0.289 (both P<0.001), reflecting strong consensus among experts. The finalized system consists of 6 first-level indicators—Moral Cultivation (0.1926), Professional Competence (0.1894), Theoretical Knowledge (0.1658), Practical Ability (0.2146), Social Engagement (0.1285), and Social Evaluation (0.1091)—along with 18 second-level and 52 third-level indicators. The resulting index system demonstrates scientific validity and practical utility, providing a structured tool for evaluating and fostering comprehensive competencies in MNS postgraduate training.